Host-microbe-cancer interactions on-a-chip - Sousa, Mauricio G. C.; Brasino, Danielle S. K.; Krieger, Madeline; Dindar, Duygu A.; Duhen, Rebekka; Zhang, Zhenzhen; Franca, Cristiane Miranda; Bertassoni, Luiz E. (Frontiers in Bioengineering and Biotechnology, 2025)
The tumor microbiota has emerged as a pivotal contributor to a variety of cancers, impacting disease development, progression, and therapeutic resistance. Due to the complexity of the tumor microenvironment, reproducing the interactions between the microbes, tumor cells, and the immune system remains a great challenge for both in vitro and in vivo studies. To this end, significant progress has been made toward leveraging tumor-on-a-chip model systems to replicate critical hallmarks of the native disease in vitro. These microfluidic platforms offer the ability to mimic essential components of the tumor microenvironment, including controllable fluid flow conditions, manipulable extracellular matrix dynamics, and intricate 3D multi-cellular communication. The primary objective of this review is to discuss recent challenges and advances in engineering host-microbiota and tumor interactions on-a-chip. Ultimately, overcoming these obstacles will help us gain deeper insights into tumor-microbe interactions and enhance avenues for developing more effective cancer therapies.